Characterization of Online Graphene Oxide and Reduced Graphene Oxide using optical diagnostics - Looi, Horace (University of Waterloo, 2025)
Graphene is a promising nanomaterial due to its high electron mobility, large specific surface area, high thermal conductivity, high tensile strength, and flexibility. In electrical applications, pristine single-layer graphene (PG) offers superior properties compared to conventional materials in semiconductors, supercapacitors, and batteries. However, since PG is difficult to manufacture at an industrial scale, there is a need for a graphene-like material that is amenable to high-yield production. A promising candidate is the thermal reduction of graphene oxide (GO) into reduced graphene oxide (rGO), which allows for high throughput of material while minimizing human intervention. However, the properties of rGO are heavily dependent on the quality of incoming GO and the resulting morphology and composition of the rGO. Therefore, a method to measure the GO and rGO properties in real time is needed. Time-resolved laser-induced incandescence (TiRe-LII) and line-of-sight attenuation (LOSA) are two absorption-based measurements that are commonly used to characterize soot and other nanomaterials in real time. Consequently, these methods are thought to have high potential in characterizing GO and rGO. In this work, ex situ methods were used to provide morphological and optical characteristics of GO. Additionally, TiRe-LII and LOSA testing were performed to assess their capabilities in measuring GO and rGO in real-time. The results show that TiRe-LII is capable of providing the relative specific surface area (SSA) of rGO, with accurate SSA trends and slight deviations in absolute value compared to ex situ testing. However, GO showed no incandescent signals due to its low absorption characteristics.LOSA testing showed that, by applying the Lorentz-Drude model, the electrical conductivity and degree of reduction of GO and rGO could be derived. The results indicated that the derived electrical conductivity matched expected trends and were similar in magnitude to literature results. This study found that TiRe-LII can be used to derive the SSA of rGO, and LOSA can be used to derive the electrical conductivity of GO and rGO, both in real time.